Formed dielectric component cross-linked by irradiation and method for making the same

By mixing and forming composite materials under product plastic conditions, and through radiation cross -linking thermoplastic polymers, it is difficult to create the problem of being able to withstand the pelvic background temperature and low -agent loss of the formation of the forming dielectric components in the existing technology. Macro -resistance and low -agent loss component manufacturing.

CN114729156BActive Publication Date: 2025-01-28ROGERS CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080080246.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-22
Filing Date
2020-11-18
Publication Date
2025-01-28
Estimated Expiration
2040-11-18

AI Technical Summary

Technical Problem

The prior art is difficult to manufacture a shaped dielectric assembly that can withstand solder reflow temperature and has low dielectric loss under commercial plastic conditions.

Method used

By melting and forming by molting thermoplastic polymer, cross -linking assistant, curing cause, additive composition, and ceramic filler composition, it forms a solid -to -plastic polymer to form a solid formation dielectric component through radiation.

Benefits of technology

It is achieved at a low processing temperature to create a formal dielectric component with high heat resistance, low -agency loss and stable size, which can withstand the return temperature of the solder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003901997090000151
    Figure GDA0003901997090000151
  • Figure GDA0003901997090000161
    Figure GDA0003901997090000161
  • Figure GDA0003901997090000171
    Figure GDA0003901997090000171
Patent Text Reader

Abstract

A cured shaped dielectric component comprising a cross-linked product of a composite material comprising a thermoplastic polymer, an optional cross-linking aid, an optional cure initiator, an optional additive composition, and a ceramic filler composition; wherein the cured shaped dielectric component has a dielectric constant of 1.1 to 20 at 10 GHz; and wherein the cured shaped dielectric component has no melt flow index when tested at 190°C, 2.16 kg according to ASTM D1238-20.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Patent Application Serial No. 62 / 938,983, filed on November 22, 2019. The related application is incorporated herein by reference in its entirety. Background Art

[0003] Many high frequency applications require polymer components with low dielectric losses. Dielectrics in components for such applications benefit from thermoplastic materials that offer ease and speed of processing, but in order to have thermal stability sufficient to pass solder reflow testing, the material needs to have a softening temperature above 300 degrees Celsius (°C). Such materials may be particularly relevant to antennas, key components in any transmission system or wireless communication infrastructure, such as in cellular base station antennas or in digital applications requiring high data transmission rates.

[0004] Both thermoplastics and thermosets have been described for use in dielectric components. Typically, thermoplastics with adequate solder reflow heat resistance (e.g., temperatures of 240°C to 280°C) used to form dielectric components have high viscosities and require extremely high processing temperatures, often requiring special barrel, screw, and heater materials. While thermosets can withstand higher processing temperatures after crosslinking, they are not suitable for a wide range of plastic processing methods, such as extrusion, injection molding, blow molding, thermoforming, and rotational molding.

[0005] In view of the above, there remains a need for improved composite materials for use as shaped dielectric components. Specifically, there is a need for materials that are easily formed into shaped dielectric components under commodity plastic conditions, that can withstand exposure to solder reflow temperatures and that have low dielectric losses. Summary of the invention

[0006] Disclosed herein are cured shaped dielectric components, methods of making, and articles including the cured shaped dielectric components.

[0007] Disclosed herein is a cured shaped dielectric component comprising a cross-linked product of a composite material comprising a thermoplastic polymer, an optional cross-linking aid, an optional curing initiator, an optional additive composition, and a ceramic filler composition; wherein the cured shaped dielectric component has a dielectric constant of 1.1 to 20 at 10 GHz; and wherein the cured shaped dielectric component has no melt flow index when tested at 190°C and 2.16 kg according to ASTM D1238-20.

[0008] The method of making a cured shaped dielectric component comprises: compounding a composite material comprising a thermoplastic polymer, an optional crosslinking aid, an optional cure initiator, an optional additive composition, and a ceramic filler composition; melting the compounded composite material to form a melt; shaping the melt to form a shaped article; and exposing the shaped article to radiation to generate sufficient free radicals in the thermoplastic polymer to crosslink at least a portion of the thermoplastic polymer to form a cured shaped dielectric component.

[0009] Articles of manufacture including the cured shaped dielectric component are also disclosed.

[0010] The above described and other features are exemplified by the following detailed description and claims. DETAILED DESCRIPTION

[0011] The present invention describes a shaped dielectric component cross-linked using radiation, and a method for making the component. It was unexpectedly found that after irradiation, the electrical properties of the cured shaped component produced from a thermoplastic polymer are maintained, and the heat resistance is improved to that of a thermosetting plastic. The cured shaped component has low dielectric losses and can withstand solder reflow. In particular, the cured shaped component can be easily manufactured by forming a composite material comprising a thermoplastic polymer. The composite material is shaped, such as molded; and the shaped composite material is then irradiated to cross-link the thermoplastic polymer. The resulting cured shaped component is thermally stable and exhibits low dimensional change.

[0012] Thus, the cured shaped dielectric component comprises a cross-linked product of a composite material comprising a thermoplastic polymer having a low processing temperature, an optional cross-linking aid, an optional curing initiator, an optional additive composition, and a ceramic filler composition. The cured shaped dielectric component has a dielectric constant of 1.1 to 20 at 500 megahertz (MHz) to 10 gigahertz (GHz), a heat resistance of up to 280 degrees Celsius (°C), or both, and has no flow at the low processing temperature used to form the cured shaped component.

[0013] The cured component is obtained by crosslinking (curing) of a thermoplastic polymer. Preferably, the thermoplastic polymer is solid at room temperature and can undergo multiple melting and solidification cycles without crosslinking (in the absence of irradiation). The thermoplastic polymer that can be used can be processed at a temperature of 280°C or less or 220°C or less and as low as 150°C, i.e., compounded into pellets and formed into shapes (i.e., by injection molding, profile extrusion, blow molding, rotational molding, extrusion, melt casting or three-dimensional printing). For example, the thermoplastic polymer can be processed at a low processing temperature of 150°C to 280°C, or 160°C to 280°C, or 160°C to 220°C, or 170°C to 200°C, or 170°C to 190°C. The thermoplastic polymer can be processed at 150°C to 235°C.

[0014] For example, the melting temperature (Tm) or glass transition temperature (Tg) of the thermoplastic polymer may be 250° C. or less, or 90° C. to 250° C. Tg may be determined by differential scanning calorimetry (DSC), for example, from −120° C. to 300° C. at a heating rate of 10° C. / min under a nitrogen blanket. Alternatively or additionally, the thermoplastic polymer may have a melt flow index (MFI) of at least 5 grams / 10 minutes (g / 10 minutes) measured at 190° C., 2.16 kilograms (kg) according to ASTM D1238-20, preferably at least 10 g / 10 minutes measured at 190° C., 2.16 kg according to ASTM D1238-20.

[0015] Exemplary thermoplastic polymers that can be crosslinked by irradiation include thermoplastic polyolefins and copolymers thereof. Exemplary polyolefins include polyethylene (including low density polyethylene (LDPE) and linear low density polyethylene (LLDPE)), polypropylene (PP), and polymethylpentene (PMP). Additional low temperature processing thermoplastics include: fluoropolymers, such as fluorinated ethylene propylene copolymers (EFEP); cyclic olefin polymers, such as polynorbornene and copolymers containing norbornene-based units and acyclic olefins (such as ethylene or propylene); and styrene block copolymers, such as styrene-ethylene-propylene-styrene block copolymers (SEPS). Combinations of thermoplastic polymers may also be used.

[0016] As described in further detail below, the amount of each component in the cross-linkable composite material can be adjusted to obtain the desired thermal and electrical properties. Most widely, if a self-crosslinking polymer such as polyethylene is used, the cross-linkable composite material can have a thermoplastic polymer up to 100 weight percent (wt%). However, there is usually at least 1 weight % of a cross-linking aid, a curing initiator, a ceramic filler composition, or one or more of other optional additives. In one aspect, based on the gross weight of the composite material, the composite material for forming the component comprises 10 weight % to 99 weight %, or 10 weight % to 95 weight %, or 50 weight % to 99 weight %, or 50 weight % to 95 weight %, or 60 weight % to 90 weight %, or 10 weight % to 50 weight %, or 10 weight % to 30 weight %, or 10 weight % to 25 weight %, or 10 weight % to 20 weight % of thermoplastic polymer.

[0017] When the thermoplastic polymer includes polyethylene, such as LDPE or LLDPE, a crosslinking aid is not required for crosslinking by irradiation, although the inclusion of a crosslinking aid can increase the crosslink density. When there is no crosslinking aid in the composite material, the crosslinked product (cured shaped dielectric component) does not contain residues of the crosslinking aid. When the thermoplastic polymer does not crosslink or undergoes fracture in the absence of a crosslinking aid, a crosslinking aid is present in the composite material to crosslink the thermoplastic polymer upon irradiation. For example, if the thermoplastic polymer includes a polymer other than polyethylene, such as polypropylene, a crosslinking aid may be present. When a crosslinking aid is present, the crosslinked product typically contains residues of the crosslinking aid.

[0018] Exemplary crosslinking aids include triallyl cyanurate, triallyl isocyanurate, triallyl trimellitate, functional phosphazenes, triallyl phosphates, polybutadiene, zinc carboxylates (e.g., zinc diacrylate and zinc dimethacrylate), vinyl terminated compounds (e.g., divinylbenzene and vinyl terminated polyphenylene ether oligomers), metaphenylene bismaleimide, multifunctional (meth) acrylates (e.g., trimethylolpropane trimethacrylate), tetramethylene glycol diacrylate, trifunctional acrylates, dipentaerythritol pentaacrylate, and combinations thereof. Incorporation of a crosslinking aid such as a functional phosphazene can be beneficial because it can also act as a flame retardant. An example is trivinyl functional phosphazenes, such as SPV-100 commercially available from Otsuka. Incorporation of a crosslinking aid such as triallyl trimellitate can reduce smoke generation.

[0019] In one aspect, the cross-linkable composite material for forming the component comprises 0 wt % to 10 wt %, or 0.25 wt % to 10 wt %, or 0.5 wt % to 8 wt %, or 1 wt % to 3 wt % of a cross-linking aid, based on the total weight of the composite material.

[0020] The crosslinkable composite material may also optionally include a curing initiator. Suitable curing initiators form initiating substances, preferably free radicals, when absorbing radiation. Photoinitiator systems may be used, including photoinitiators that form free radicals by extracting hydrogen or electrons from a second compound when irradiated, the second compound being generally referred to as a co-initiator, which provides initiating free radicals. Curing (crosslinking) may be achieved by more than one type of radiation with different wavelengths. In some cases, it may be preferred to use more than one type of curing initiator simultaneously.

[0021] Examples of specific curing initiators include quinones, benzophenones and substituted benzophenones, hydroxyalkylphenylacetophenones, dialkoxyacetophenones, α-halo-acetophenones, aryl ketones (e.g., 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 2-benzyl-2-dimethylamino-(4-morpholinophenyl)butan-1-one), thioxanthones (e.g., isopropylthioxanthones), benzil dimethyl ketal, Bis(2,6-dimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide, trimethylbenzoylphosphine oxide derivatives (e.g. 2,4,6-trimethylbenzoyldiphenylphosphine oxide), methylthiophenylmorpholinone (e.g. 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one), morpholinophenylaminoketone, 2,2-dimethoxy-l,2-diphenylethan-l-one, 5,7-diiodo-3-butoxy-6-fluorone, diphenyliodonium Fluoride, triphenyl Hexafluorophosphate, benzoin ether, peroxide, bisimidazole, aminoketone, benzoyl oxime ester, camphorquinone, coumarin ketone, Michler's ketone, poly (1,4-diisopropylbenzene) (CUROX from United initiators TM CC-P3) and 2,3-dimethyl-2,3-diphenylbutane. Suitable curing initiators are available, for example, under the trade name IRGACURE TM (from BASF), LUCERIN TM TPO (from BASF AG), PERKADOX TM (from Nouryon) and ESACURE TM (from LAMBERTI). In one aspect, the curing initiator has an initiation temperature or degradation temperature that is higher than the processing temperature of the thermoplastic polymer, for example, at least 10°C, at least 20°C, or at least 30°C higher than the processing temperature of the thermoplastic polymer. For example, if compounding is performed at 180°C and molding is performed at 190°C, it is preferred that the curing initiator does not degrade during these processes. For example, PERKADOXTM The half-life temperature of 30 is 284° C. at 0.1 hour, 259° C. at 1 hour, and 237° C. at 10 hours. The curing initiator may have a half-life of 0.05 to 1 hour at 284° C., or a half-life of 0.5 to 5 hours or 0.5 to 2 hours at 259° C., or a half-life of 5 to 15 hours at 237° C. Compounding or molding is typically performed at a residence time of 2 to 10 minutes to minimize degradation of the curing agent.

[0022] The curing initiator may be present in an amount of 0 wt % to 5 wt %, or 0.01 wt % to 5 wt %, or 0.1 wt % to 3 wt %, or 1 wt % to 2 wt %, based on the total weight of the composite.

[0023] The composite materials described herein may also include a ceramic filler composition for adjusting the dielectric or other properties of the formed and cured component. Preferably, the ceramic filler composition is present. The ceramic filler composition may include at least one of the following: fumed silica, titanium dioxide, barium titanate, strontium titanate, corundum, wollastonite, Ba2Ti9O 20 , hollow ceramic balls, boron nitride, aluminum nitride, silicon carbide, beryllium oxide, aluminum oxide, trihydrate aluminum oxide, magnesium oxide, mica, talc, nano clay, magnesium hydroxide, solid glass balls, hollow glass balls, or a combination thereof. The ceramic filler composition may include silicon dioxide, titanium dioxide, or a combination thereof. The titanium dioxide particles may be irregular shapes with multiple flat surfaces. The D90 particle size by weight of the ceramic filler may be 0.1 micron to 10 microns or 0.5 microns to 5 microns. The D90 particle size by weight of the ceramic filler may be less than or equal to 2 microns or 0.1 microns to 2 microns.

[0024] In one aspect, the ceramic filler composition has a multimodal particle size distribution, wherein the peak of the first mode of the multimodal particle size distribution is at least seven times the peak of the second mode of the multimodal particle size distribution. Multimodal particle size distribution can achieve a composite material with a lower viscosity. Multimodal particle size distribution can be, for example, bimodal, trimodal, or quadrimodal. In other words, the ceramic filler can include a first plurality of particles with a first average particle size and a second plurality of particles with a second average particle size, wherein the first average particle size is greater than or equal to 7 times, or greater than or equal to 10 times, or 7 to 60 times, or 7 to 20 times the second average particle size. As used herein, the term particle size refers to the diameter of a sphere having the same volume as a particle, and the average particle size refers to the numerical average of the particle sizes of a plurality of particles. The peak of the first mode (the first average particle size) can be greater than or equal to 2 microns, or 2 to 20 microns. The peak of the second mode (second average particle size) may be greater than or equal to 0.2 micrometers, or less than or equal to 2 micrometers, or between 0.2 micrometers and 1.5 micrometers.

[0025] The first plurality of particles and the second plurality of particles can contain the same ceramic filler. For example, the first plurality of particles and the second plurality of particles can contain titanium dioxide. Conversely, the first plurality of particles and the second plurality of particles can contain different ceramic fillers. For example, the first plurality of particles can contain silicon dioxide and the second plurality of particles can contain titanium dioxide.

[0026] The first plurality of particles may have an average particle size of 1 to 10 microns, or 2 to 5 microns. The second plurality of particles may have an average particle size of 0.01 to 1 micron, or 0.1 to 0.5 microns. The ceramic filler may include a first plurality of particles comprising titanium dioxide having an average particle size of 1 to 10 microns and a second plurality of particles having an average particle size of 0.1 to 1 micron.

[0027] The ceramic filler composition can be present in an amount of 1 wt % to 90 wt %, or 5 wt % to 90 wt %, or 1 wt % to 50 wt %, or 5 wt % to 50 wt %, or 10 wt % to 40 wt %, or 50 wt % to 90 wt %, or 70 wt % to 90 wt %, or 75 wt % to 90 wt %, or 80 wt % to 90 wt %, based on the total weight of the composite.

[0028] In another aspect, the composite material comprises greater than 20 volume percent (vol %) ceramic filler, based on the total volume of the composite material.

[0029] In one aspect, the composite material comprises greater than 40 volume percent ceramic filler, based on the total volume of the composite material.

[0030] The ceramic filler can include treated titanium dioxide. For example, the titanium dioxide can be sintered to increase the amount of the desired phase. Without wishing to be bound by theory, it is believed that sintering can help the composition achieve lower dielectric losses. The first plurality of titanium dioxide particles having an average particle size of 1 to 10 microns, or 2 to 5 microns can be sintered. The first plurality of titanium dioxide particles having an average particle size of 0.1 to 1 micron, or 0.1 to 0.5 microns can be sintered.

[0031] The ceramic filler can be surface treated, for example, with a surfactant, silane, titanate, zirconate, organic polymer or other inorganic material to facilitate dispersion into the thermoplastic polymer. For example, the particles can be coated with a surfactant such as oleylamine oleic acid or the like. The silane can include N-β (aminoethyl) -γ-aminopropyl triethoxysilane, N-β (aminoethyl) -γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, 3-chloropropyl-methoxysilane, γ-glycidoxypropyl triethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-methacryloxypropyl trieth ... The silane may include phenyl silane. The silane may include substituted phenyl silanes, such as those described in U.S. Pat. No. 4,756,971. The titanate coating can be formed from the following: isostearyl titanate [tri(isooctadecyloxy-O)(prop-2-oxy)titanium]; neopentyl(diallyl)oxy, trineodecanoyl titanate; neopentyl(diallyl)oxy, tri(dodecyl)benzene-sulfonyl titanate; neopentyl(diallyl)oxy, tri(dioctyl)phosphate titanate; neopentyl(diallyl)oxy, tri(dioctyl)pyrophosphate titanate; neopentyl(diallyl)oxy, tri(N-ethylenediamino)ethyl titanate; neopentyl(diallyl)oxy, tri(m-amino)phenyl titanate; and neopentyl(diallyl)oxy, trihydroxyhexanoyl titanate; or a combination thereof. In one aspect, the titanate coating is isostearyl titanate [tri(isooctadecyloxy-O)(prop-2-oxy)titanium], such as TYTAN TMCP-317 (Borica). The zirconate coating may be formed of neopentyl (diallyloxy) tris (dioctyl) pyrophosphate zirconate, neopentyl (diallyloxy) tris (N-ethylenediamino) ethyl zirconate, or a combination thereof.

[0032] The coating may be present at 0.01 wt % to 2 wt %, or 0.1 wt % to 1 wt %, based on the total weight of the coated ceramic filler. The ceramic filler may be coated with SiO2, Al2O3, MgO, or a combination thereof. The ceramic filler may be coated by a base catalyzed sol-gel technique, a polyetherimide (PEI) wet and dry coating technique, or a poly(ether ketone) (PEEK) wet and dry coating technique.

[0033] In one aspect, the composite material comprises an additive composition for adjusting the desired properties of the cured shaped component. The additive composition may include an antioxidant, a metal passivator, a processing aid (e.g., polyethylene wax or a stearic acid derivative), an adhesion promoter, or a combination thereof. A non-limiting example of an antioxidant is commercially available from BASF under the trade name CHIMASSORB TM 944 poly[[6-(1,1,3,3-tetramethylbutyl)amino-s-triazine-2,4-diyl][(2,2,6,6,-tetramethyl-4-piperidinyl)imino]hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl-)imino]], or IRGANOX TM 1010 (pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate)). A non-limiting example of a metal deactivator is commercially available from ADDIVANT TM The product name is NAUGARD TM 2,2-oxalyl diamidobis[ethyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate of XL-1. A preferred metal deactivator is SONGNOX commercially available from Songwon. TM 1024 1,2-bis(3,5-di-tert-butylhydroxyhydrocinnamoyl)hydrazine. Exemplary processing aids include Honeywell A-C TM 6ALDPE wax. Exemplary adhesion promoters include maleic anhydride grafted polyolefins such as SCONA TM TSPE 1112GALL.

[0034] Each additive, when present, can be used in an amount of 0% to 2% by weight, or 0.0001% to 2% by weight, or 0.0005% to 1.6% by weight, based on the total weight of the composite material. Typically, the additive composition can be present in a total amount of 0.0001% to 5% by weight, or 0.001% to 3% by weight, each based on the total weight of the composite material.

[0035] Thus, a method of making a cured shaped dielectric component can include compounding a composite material comprising a thermoplastic polymer having a low processing temperature, an optional crosslinking aid, an optional curing initiator, an optional additive composition, and a ceramic filler composition. The compounded composite material can be melted to form a melt, and the melt is shaped to form a shaped article. The shaped article can then be exposed to radiation to generate sufficient free radicals in the thermoplastic polymer to crosslink at least a portion of the thermoplastic polymer to form a cured shaped dielectric component.

[0036] In the method of making a cured shaped dielectric component, compounding can be carried out on known equipment suitable for melting and blending thermoplastic polymers, such as a single screw extruder or a twin screw extruder, a Buss co-kneader, a Farrel continuous mixer, a Banbury mixer, or a two-roll mill. The various ingredients can be mixed directly or fed sequentially. In one aspect, the composite is extruded into strands and cut into cylindrical pellets. Compounding or other processing can be carried out at a temperature of 150°C to 250°C, or 160°C to 220°C, or 170°C to 200°C, or 170°C to 190°C.

[0037] After compounding, the crosslinkable composite may have an MFI of at least 5 g / 10 min measured at 190° C., 2.16 kg according to ASTM D1238-20, preferably at least 10 g / 10 min measured at 190° C., 2.16 kg according to ASTM D1238-20.

[0038] The cross-linkable composite material can then be melted and shaped. Melting and shaping can be carried out at a temperature of 150°C to 250°C, or 160°C to 220°C, or 170°C to 200°C, or 170°C to 190°C. Shaping can be achieved, for example, by molding (e.g., injection molding, rotational molding or blow molding), extrusion (e.g., extrusion profiles or layers), or other ways of forming layers to form solid shapes, sheets, layers, rods, tubes or hollow products. For example, shaping can include forming layers on a copper substrate such as a conductive copper layer. In a preferred aspect, shaping is achieved by molding. In one aspect, a foaming agent can be added during melting and shaping to provide a low-density shape, sheet, rod or tube. In one aspect, the molten cross-linkable composite material can be injected into a mold or overmolded onto a substrate to provide a shaped product and minimize secondary processing and bonding processes.

[0039] The shaped article can be irradiated to generate free radicals on the polymer backbone or side chains, thereby initiating crosslinking and forming a three-dimensional network in the cured shaped component. Exemplary irradiation methods include electron beam irradiation, gamma irradiation, ultraviolet irradiation, and the like.

[0040] In another aspect, the composite is melted and shaped on a substrate, and the substrate is irradiated. A mask may be used to cover areas of the substrate to be protected from irradiation. Thus, in one aspect, a shaped article is formed on a substrate, a mask is used to cover radiation-sensitive areas of the substrate to be protected from irradiation, and unmasked areas of the shaped article are exposed to irradiation, thereby providing crosslinking of the shaped article while protecting the radiation-sensitive areas of the substrate.

[0041] The cured shaped component comprises the cured product of the composite material, particularly the cross-linked product of the thermoplastic polymer and any residual cross-linking aid, curing agent and additive (if used), and the ceramic filler composition. Of course, if no cross-linking aid, curing agent or additive is present in the composite material, no residual cross-linking aid, curing agent or additive will be present.

[0042] Importantly, after curing, the shaped dielectric component has no melt flow at the above processing temperatures, for example, at 150° C. to 250° C., or 160° C. to 220° C., or 170° C. to 200° C., or 170° C. to 190° C. As used herein, the phrase "no melt flow" may mean that the MFI is equal to 0 g / 10 minutes. This feature may be characterized in that the shaped dielectric component has no (i.e., unmeasurable) MFI when tested according to ASTM D1238-20 at 190° C., 2.16 kg.

[0043] The cured shaped dielectric component may have a dielectric constant (relative dielectric constant, Dk) of 1.1 to 20 in the range of 500 MHz to 10 GHz. The cured shaped dielectric component may have a heat resistance of at least to 250° C. The cured shaped dielectric component may be dimensionally stable, such that the dimensional change of the cured shaped dielectric component at a temperature up to 280° C. is less than 5%, or 0% to 1%.

[0044] In one aspect, the dielectric constant of the cured shaped dielectric component can be greater than 1.1, such as 1.5 to 20, or 2.5 to 20, or 3 to 18, or 3 to 13, when measured at 10 GHz. In one aspect, the dielectric constant of the cured shaped dielectric component measured at 10 GHz is less than 6. In another aspect, the dielectric constant of the cured shaped dielectric component can be greater than 1.1, such as 1.6 to 6, or 1.5 to 6, or 2 to 6, when measured at 10 GHz. In yet another aspect, the dielectric constant of the cured shaped dielectric component can be greater than 6, or greater than 10, or greater than 12, such as 6 to 20, or 6 to 18, or 6 to 15, or 10 to 20, or 12 to 20, when measured at 10 GHz.

[0045] The dielectric loss (Df) of the cured shaped dielectric component can be less than or equal to 0.007, or less than or equal to 0.005. When measured at 10 GHz, the dielectric loss can be as low as 0.001. For example, the dielectric loss of the cured shaped dielectric component at 10 GHz can be 0.001 to 0.005.

[0046] The dielectric properties may be measured at a temperature of 23°C to 25°C according to the "Stripline Test for Permittivity and Loss Tangent at X-Band" test method IPC-TM-650 2.5.5.5.

[0047] The cured formed dielectric assembly can pass a solder float test at 288°C for 30 seconds without cracking, blistering or warping of the assembly.

[0048] The linear dimensional change of the component before curing compared to after curing may be less than 2%, preferably less than 1% in at least one, two, three or all linear dimensions such as diameter, length, height, width, etc. In one aspect, the linear dimensional change of the component before curing compared to after curing may be less than 2%, preferably less than 1% in two or three linear dimensions.

[0049] In another aspect, the change in volume size of the component before curing compared to after curing may be less than 2%, preferably less than 1%.The volume change may be measured, for example, by three-dimensional imaging.

[0050] Advantageously, the use of thermoplastic polymers allows the production of cured shaped dielectric components using standard equipment. Furthermore, by using radiation to crosslink the shaped dielectric components, the cured components can be operated at temperatures much higher than those of thermoplastics. The cured shaped dielectric components have heat resistance that is not affected by solder reflow processing at 240°C to 280°C.

[0051] Circuit materials including the cured shaped dielectric components described herein can be prepared by forming a multilayer material having a base layer including the cured shaped dielectric component and a conductive layer arranged thereon. Available conductive layers include, for example, stainless steel, copper, gold, silver, aluminum, zinc, tin, lead, transition metals, and alloys thereof. There are no particular restrictions on the thickness of the conductive layer, nor are there any restrictions on the shape, size, or surface texture of the conductive layer. The thickness of the conductive layer can be 3 microns to 200 microns, or 9 microns to 180 microns. When there are two or more conductive layers, the thickness of the two layers can be the same or different. The conductive layer can include a copper layer. Suitable conductive layers include thin layers of conductive metals, such as copper foils currently used to form circuits, such as electro-deposited copper foils. The root mean square (RMS) roughness of the copper foil can be less than or equal to 2 microns, or less than or equal to 0.7 microns, wherein the roughness is measured using Veeco Instruments WYCO TM Optical profilometers use white light interferometry to measure.

[0052] The conductive layer can be applied by laminating the conductive layer to the substrate, by direct laser structuring, or by adhering the conductive layer to the substrate via an adhesive layer. Where the specific material and form of the circuit material permit, other methods known in the art may be used to apply the conductive layer, such as electrodeposition and chemical vapor deposition.

[0053] Lamination may require lamination of a multilayer stack including a substrate, a conductive layer and an optional intermediate layer between the substrate and the conductive layer to form a layered structure. The conductive layer can be in direct contact with the substrate layer without an intermediate layer. The layered structure can then be placed in a press (e.g., a vacuum press) at a certain pressure and temperature and continue to be suitable for combining the layers and forming a laminate. Lamination and optional curing can be performed by a one-step process, such as using a vacuum press, or can be performed by a multi-step process. In a one-step process, the layered structure can be placed in a press, raised to a lamination pressure (e.g., 150 pounds per square inch (psi) to 400psi (1 MPa to 2.8 MPa)) and heated to a lamination temperature (e.g., 260°C to 390°C). The lamination temperature and pressure can maintain a desired holding time, such as 20 minutes, followed by cooling (while still under pressure) to less than or equal to 150°C.

[0054] If present, the intermediate layer may include a polyfluorocarbon film that may be positioned between the conductive layer and the substrate layer, and an optional microglass reinforced fluorocarbon polymer layer may be positioned between the polyfluorocarbon film and the conductive layer. The microglass reinforced fluorocarbon polymer layer may improve the adhesion of the conductive layer to the substrate. The microglass may be present in an amount of 4 weight percent (wt%) to 30 wt%, based on the total weight of the layer. The longest length scale of the microglass may be less than or equal to 900 microns, or less than or equal to 500 microns. The microglass may be a type of microglass such as that commercially available through Johns-Manville Corporation of Denver, Colorado. The polyfluorocarbon film comprises a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), a fluorinated ethylene-propylene copolymer (e.g., TEFLON TM FEP), and copolymers having a tetrafluoroethylene backbone and fully fluorinated alkoxy side chains (e.g., TEFLON TM PFA)).

[0055] The conductive layer can be applied by laser direct structuring. Here, the substrate can include a laser direct structuring additive, and the laser direct structuring can include irradiating the surface of the substrate with a laser, forming a track of the laser direct structuring additive, and applying a conductive metal to the track. The laser direct structuring additive can include metal oxide particles (e.g., titanium oxide and copper chromium oxide). The laser direct structuring additive can include spinel-based inorganic metal oxide particles, such as spinel copper. The metal oxide particles can be coated, for example, with a composition comprising tin and antimony (e.g., 50% to 99% by weight of tin and 1% to 50% by weight of antimony based on the total weight of the coating). Based on 100 parts of the corresponding composition, the laser direct structuring additive can include 2 to 20 parts of the additive. Irradiation can be performed with a YAG laser with a wavelength of 1,064 nanometers (nm) at an output power of 10 watts (W), a frequency of 80 kilohertz (kHz), and a rate of 3 meters / second (m / second). A conductive metal can be applied in an electroless plating bath comprising, for example, copper using a plating process.

[0056] Conductive layer can be applied by adhesively applying conductive layer.Conductive layer can be circuit (metallization layer of another circuit), such as flexible circuit.Adhesive layer can be arranged between one or more conductive layers and substrate.When suitable, adhesive layer can comprise poly (arylene ether) and carboxyl functionalized polybutadiene or polyisoprene polymer, and described carboxyl functionalized polybutadiene or polyisoprene polymer comprises butadiene, isoprene or butadiene unit and isoprene unit and 0 wt % to 50 wt % co-curable monomer unit.Adhesive layer can exist with the amount of 2 g / m2 to 15 g / m2.Poly (arylene ether) can comprise carboxyl functionalized poly (arylene ether).Poly (arylene ether) can be the reaction product of poly (arylene ether) and cyclic anhydride or the reaction product of poly (arylene ether) and maleic anhydride.Carboxyl functionalized polybutadiene or polyisoprene polymer can be carboxyl functionalized butadiene-styrene copolymer. The carboxyl functionalized polybutadiene or polyisoprene polymer may be the reaction product of a polybutadiene or polyisoprene polymer and a cyclic anhydride. The carboxyl functionalized polybutadiene or polyisoprene polymer may be a maleated polybutadiene-styrene or a maleated polyisoprene-styrene copolymer.

[0057] The cured shaped dielectric components can be used in electronic devices and electromagnetic components, such as inductors on electronic integrated circuit chips, electronic circuits, electronic packaging, modules, housings, transducers, ultra-high frequency (UHF) antennas, very high frequency (VHF) antennas and microwave antennas for various applications such as power applications, data storage and microwave communications. The cured shaped dielectric components can be used in electronic devices, such as mobile Internet devices. The cured shaped dielectric components can be used in electronic devices, such as mobile phones, tablets, laptops and networked watches. The cured shaped dielectric components can be used in applications where an external DC magnetic field is applied. In addition, the cured shaped dielectric components can be used with very good results (size and bandwidth) in all antenna designs in the frequency range of 1 GHz to 10 GHz. The antenna can be a planar inverted F antenna, a patch antenna, a dipole antenna, or a meander line antenna. In one aspect, the cured shaped dielectric component is the dielectric portion of a dielectric resonator antenna. The cured shaped dielectric component can be a resonator. The cured shaped dielectric component can be a dielectric resonator antenna. The cured shaped dielectric component can be an electromagnetic waveguide, including but not limited to a dielectric waveguide or a metal waveguide with a dielectric in the transmission region. The cured shaped dielectric component can be a dielectric electromagnetic lens, for example, a dielectric electromagnetic lens configured to operate at a frequency greater than 5 GHz and less than 300 GHz. The cured shaped dielectric component can be used in a radio frequency (ratio-frequency, RF) component. The cured shaped dielectric component can be used in a microwave component. The cured shaped dielectric component can be used in a millimeter wave component. The cured shaped dielectric component can be used in a terahertz component. The cured shaped dielectric component can be used in an optical component.

[0058] The cured shaped dielectric component (also referred to as component) may include a crosslinked product of a composite material. The composite material may include a thermoplastic polymer and a ceramic filler composition. The composite material may optionally include at least one of a crosslinking aid, a curing initiator, or an additive composition. The dielectric constant of the component at 10 GHz may be 1.1 to 20. When tested at 190°C, 2.16 kg according to ASTM D1238-20, the component may have no melt flow index. The processing temperature of the thermoplastic polymer may be 160°C to 280°C. The melting temperature of the thermoplastic polymer may be 250°C or lower, or 90°C to 250°C. The thermoplastic polymer may have a melt flow index of less than 5 g / 10 minutes measured at 190°C, 2.16 kg according to ASTM D1238-20. The thermoplastic polymer may include polyethylene, polypropylene, polymethylpentene, fluorinated ethylene propylene copolymer, polynorbornene, styrene-ethylene-propylene-styrene block copolymer, or a combination thereof. The thermoplastic polymer may include low density polyethylene or linear low density polyethylene. The cross-linked product may include residues of a cross-linking aid. On the contrary, the cross-linked product may not contain residues of a cross-linking aid, for example, if the thermoplastic polymer includes a thermoplastic polymer such as polyethylene that self-crosslinks when irradiated. The composite material may include a curing initiator and it may have an initiation temperature higher than the processing temperature of the thermoplastic polymer, preferably at least 10°C, at least 20°C, or at least 30°C higher than the processing temperature of the thermoplastic polymer. The composite material may include all three of a cross-linking aid, a curing initiator, and an additive composition. A cross-linking aid may be present and the cross-linking aid may include triallyl cyanurate, triallyl isocyanurate, triallyl phosphate, polybutadiene, zinc diacrylate, zinc dimethacrylate, divinylbenzene, vinyl-terminated polyphenylene ether oligomers, metaphenylene bismaleimide, trimethylolpropane trimethacrylate, tetramethylene glycol diacrylate, trifunctional acrylate, dipentaerythritol pentaacrylate, or a combination thereof. An additive composition may be present and may include an antioxidant, a metal passivator, a processing aid, an adhesion promoter, or a combination thereof. The ceramic filler may include fumed silica, titanium dioxide, barium titanate, strontium titanate, corundum, wollastonite, Ba2Ti9O 20 , hollow ceramic spheres, boron nitride, aluminum nitride, silicon carbide, beryllium oxide, aluminum oxide, aluminum oxide trihydrate, magnesium oxide, mica, talc, nanoclay, magnesium hydroxide, solid glass spheres, hollow glass spheres, or combinations thereof. The ceramic filler may have a multimodal particle size distribution, wherein the peak of a first mode of the multimodal particle size distribution is at least seven times the peak of a second mode of the multimodal particle size distribution.

[0059] The composite material before cross-linking may include 10 wt % to 99 wt % of a thermoplastic polymer, 0 wt % to 10 wt %, or 0.25 wt % to 10 wt % of a cross-linking aid, 0 wt % to 5 wt %, or 0.01 wt % to 5 wt % of a curing initiator, 0 wt % to 2 wt %, or 0.0001 wt % to 2 wt % of an additive composition, and 1 wt % to 90 wt % of a ceramic filler composition, based on the total weight of the composite material before cross-linking, and the total is 100 wt %. The composite material before cross-linking may include 50 wt % to 95 wt % of a thermoplastic polymer, 0 wt % to 10 wt %, or 0.25 wt % to 10 wt % of a cross-linking aid, 0 wt % to 5 wt %, or 0.01 wt % to 5 wt % of a curing initiator, 0 wt % to 2 wt %, or 0.001 wt % to 2 wt % of an additive composition, and 5 wt % to 50 wt % of a ceramic filler composition, based on the total weight of the composite material before cross-linking, and the total is 100 wt %. The composite material before cross-linking may include 10 wt % to 50 wt % of a thermoplastic polymer, 0 wt % to 10 wt %, or 0.25 wt % to 10 wt % of a cross-linking aid, 0 wt % to 5 wt %, or 0.01 wt % to 5 wt % of a curing initiator, 0 wt % to 2 wt %, or 0.001 wt % to 2 wt % of an additive composition, and 50 wt % to 90 wt % of a ceramic filler composition, based on the total weight of the composite material before cross-linking, and the total is 100 wt %. Based on the total weight of the composite material before crosslinking, the composite material before crosslinking may include 10 wt% to 25 wt% of thermoplastic polymer, 0 wt% to 10 wt%, or 0.25 wt% to 10 wt% of crosslinking aid, 0 wt% to 5 wt%, or 0.01 wt% to 5 wt% of curing initiator, 0 wt% to 2 wt%, or 0.001 wt% to 2 wt% of additive composition, and 75 wt% to 90 wt% of ceramic filler composition, and the total is 100 wt%. Based on the total volume of the composite material, the composite material may include more than 20 volume%, preferably more than 40 volume% of ceramic filler.

[0060] The dielectric constant of the component measured at 10 GHz may be from 1.1 to 20. If the component comprises a reduced amount of the ceramic filler composition, for example from 5 wt% to 50 wt%, based on the total weight of the composite material before crosslinking, the component may have a lower dielectric constant of from 1.1 to 6 measured at 10 GHz. If the component comprises an increased amount of the ceramic filler composition, for example from greater than or equal to 50 wt% to 90 wt%, based on the total weight of the composite material before crosslinking, the component may have a higher dielectric constant of greater than 6, preferably greater than 10, preferably greater than 12 measured at 10 GHz. The linear dimensional change of the component before curing compared to after curing is less than 2%, preferably less than 1%, in any or all linear dimensions.

[0061] The component may be a dielectric resonator antenna, a dielectric portion of a dielectric resonator antenna, an electromagnetic waveguide, a dielectric electromagnetic lens, a radio frequency component, a microwave component, a millimeter wave component, a terahertz component, or an optical component. The component may be a dielectric electromagnetic lens, preferably a dielectric electromagnetic lens configured to operate at a frequency greater than 5 GHz and less than 300 GHz. The circuit material or circuit substrate may include a cured shaped dielectric component.

[0062] A method of making a cured shaped dielectric component may include: compounding a composite material comprising a thermoplastic polymer, an optional crosslinking aid, an optional curing initiator, an optional additive composition, and a ceramic filler composition; melting the compounded composite material to form a melt; shaping the melt to form a shaped article; and exposing the shaped article to radiation to generate sufficient free radicals in the thermoplastic polymer to crosslink at least a portion of the thermoplastic polymer to form a cured shaped dielectric component. The method may also include forming the shaped article on a substrate, masking at least a portion of the shaped article from the radiation, and exposing an unmasked portion of the shaped article to the radiation to form a cured shaped dielectric component. Shaping may include molding or forming a layer, preferably molding.

[0063] The following examples are illustrative only and are not intended to limit the compositions described herein, the cured shaped assemblies, or the incorporated devices, or the procedures, conditions, or process parameters described herein.

[0064] Example

[0065] In the examples, by Tinius Olsen TM The Extrusion Plastometer measures the melt flow index (MFI) at 190°C / 2.16kg.

[0066] Thermomechanical analysis (TMA) melting points were measured by TA Instruments TMA Q400. TMA was determined according to ASTM E1545-11 (2016), where the sample was heated from -50°C to 300°C, cooled, and reheated from -50°C to 300°C, all at a rate of 10°C / min. The first thermal cycle was for annealing to eliminate orientation and extraneous physical effects, and the second heating was performed to prove that the measurement was reproducible.

[0067] Long stripline dielectric constant (LSL) was measured using a Hewlett Packard Network Analyzer 8510 and is reported at 10 GHz.

[0068] Solder float was determined at 287°C by a Ritehete solder melting unit.

[0069] The components used in the examples are provided in Table 1.

[0070]

[0071] Examples 1 to 6

[0072] The compositions of Table 2 were compounded by twin screw extrusion. The compounded compositions were formed into shapes by injection molding at 180° C. using an Extrude to Fill E30V molding machine. The formed shapes were then crosslinked using an electron beam (0 MRad, 8 MRad, 16 MRad, and 32 MRad) at room temperature. The MFI and TMA of the material before crosslinking (0 MRad) and the properties of the crosslinked shapes were determined and are shown in Table 2.

[0073]

[0074] *A mixture of titanate-treated Rogers TiO2 and Chemours R-104

[0075] Example 7

[0076] Under the same measurement conditions, the liquid crystal polymer (LCP) filled with TiO2 failed the solder float test at 5 minutes and cracks appeared.

[0077] Examples 8 to 10

[0078] Examples 8 to 10 as shown in Table 3 were prepared with (8) no crosslinking aid and no curing initiator, (9) with a crosslinking aid but no curing initiator, and (10) with both a crosslinking aid and a curing initiator, and were cured by exposure to 32 MRad of electron beam radiation.

[0079] The melting peak temperatures and melting effects of the cured compositions are also shown in Table 3.

[0080]

[0081] *A mixture of titanate-treated Rogers TiO2 and Chemours R-104

[0082] The data in Table 3 show that the polypropylene of Example 8, when exposed to an electron beam in the absence of a crosslinker or initiator, depolymerizes by cleavage, as evidenced by complete melting. The addition of a crosslinking aid as in Example 9 achieved significant improvement, but the TMA scan still showed a small feature at the melting point, indicating that there were some uncrosslinked domains, albeit in small amounts. The addition of a crosslinker and a secondary cure initiator (284°C temperature for a 0.1 hour half-life, well below the melt mixing temperature of 180°C) as in Example 10 both eliminated the last remnants of uncrosslinked polymer, as evidenced by the TMA scan showing no melting features.

[0083] Example 11: Dimensional changes

[0084] A shaped component, specifically an antenna, was formed comprising the following composition: 6.93 wt% LLDPE, 6.93 wt% HDPE, 78.95 wt% titanium dioxide, 4.95 wt% fumed silica / silane, 2.02% TAIC, 0.198 wt% PERDADOX TM 30% curing initiator, and 0.0396% by weight each of metal deactivator and antioxidant. The diameter and height of the assembly in millimeters (mm) were measured at room temperature before and after curing. The results are provided in Table 4, where samples A to E are identical samples labeled for tracking purposes.

[0085]

[0086] As can be seen from Table 4, compared with before irradiation, the diameter and height of the component after irradiation remain basically unchanged.

[0087] Non-limiting aspects of the disclosure are set forth below.

[0088] Aspect 1. A cured shaped dielectric component comprises a cross-linked product of a composite material, wherein the composite material comprises a thermoplastic polymer, an optional cross-linking aid, an optional curing initiator, an optional additive composition, and a ceramic filler composition; wherein the cured shaped dielectric component has a dielectric constant of 1.1 to 20 at 10 GHz; and wherein the cured shaped dielectric component has no melt flow index when tested at 190°C and 2.16 kg according to ASTM D1238-20.

[0089] Aspect 2. The cured shaped dielectric component according to aspect 1, wherein the processing temperature of the thermoplastic polymer is 160°C to 280°C.

[0090] Aspect 3. The cured shaped dielectric component according to any one of aspects 1 or 2, wherein the thermoplastic polymer has a melting temperature of 250°C or less, or 90°C to 250°C.

[0091] Aspect 4. The cured shaped dielectric component of any one of Aspects 1 to 3, wherein the thermoplastic polymer has a melt flow index of less than 5 g / 10 min as measured at 190° C., 2.16 kg according to ASTM D1238-20.

[0092] Aspect 5. The cured shaped dielectric component of any one of aspects 1 to 4, wherein the thermoplastic polymer comprises polyethylene, polypropylene, polymethylpentene, fluorinated ethylene propylene copolymer, polynorbornene, styrene-ethylene-propylene-styrene block copolymer, or a combination thereof.

[0093] Aspect 6. The cured shaped dielectric component of any one of Aspects 1 to 5, wherein the thermoplastic polymer comprises LDPE or LLDPE.

[0094] Aspect 7. The cured shaped dielectric component according to any one of aspects 1 to 6, wherein the cross-linked product comprises residues of a cross-linking aid.

[0095] Aspect 8. A cured shaped dielectric component according to any one of Aspects 1 to 6, wherein the cross-linked product does not contain residues of a cross-linking aid; and wherein the thermoplastic polymer comprises a thermoplastic polymer that self-cross-links upon irradiation, such as polyethylene.

[0096] Aspect 9. A cured shaped dielectric component according to any one of Aspects 1 to 8, wherein the curing initiator is present and has an initiation temperature higher than the processing temperature of the thermoplastic polymer, preferably at least 10°C, at least 20°C, or at least 30°C higher than the processing temperature of the thermoplastic polymer.

[0097] Aspect 10. A cured shaped dielectric component according to any one of Aspects 1 to 9, wherein at least one or more of the cross-linking aid, the curing initiator or the additive composition is present, preferably wherein all three of the cross-linking aid, the curing initiator and the additive composition are present.

[0098] Aspect 11. A cured shaped dielectric component according to any one of Aspects 1 to 10, wherein the crosslinking aid comprises triallyl cyanurate, triallyl isocyanurate, triallyl phosphate, polybutadiene, zinc diacrylate, zinc dimethacrylate, divinylbenzene, vinyl terminated polyphenylene ether oligomer, m-phenylene bismaleimide, trimethylolpropane trimethacrylate, tetramethylene glycol diacrylate, trifunctional acrylate, dipentaerythritol pentaacrylate, or a combination thereof.

[0099] Aspect 12. The cured shaped dielectric component of any one of aspects 1 to 11, wherein the additive composition comprises an antioxidant, a metal deactivator, a processing aid, an adhesion promoter, or a combination thereof.

[0100] Aspect 13. A cured shaped dielectric component according to any one of aspects 1 to 12, wherein the ceramic filler comprises fumed silica, titanium dioxide, barium titanate, strontium titanate, corundum, wollastonite, Ba2Ti9O 20 , hollow ceramic balls, boron nitride, aluminum nitride, silicon carbide, beryllium oxide, aluminum oxide, aluminum oxide trihydrate, magnesium oxide, mica, talc, nanoclay, magnesium hydroxide, solid glass balls, hollow glass balls, or combinations thereof.

[0101] Aspect 14. A cured shaped dielectric component according to any one of Aspects 1 to 13, wherein the ceramic filler has a multimodal particle size distribution, wherein a peak of a first mode of the multimodal particle size distribution is at least seven times greater than a peak of a second mode of the multimodal particle size distribution.

[0102] Aspect 15. A cured shaped dielectric component according to any one of Aspects 1 to 14, wherein the composite material before crosslinking comprises 10 wt% to 99 wt% of the thermoplastic polymer, 0 wt% to 10 wt%, or 0.25 wt% to 10 wt% of the crosslinking aid, 0 wt% to 5 wt%, or 0.01 wt% to 5 wt% of the curing initiator, 0 wt% to 2 wt%, or 0.0001 wt% to 2 wt% of the additive composition, and 1 wt% to 90 wt% of the ceramic filler composition, based on the total weight of the composite material before crosslinking, and the total is 100 wt%.

[0103] Aspect 16. A cured shaped dielectric component according to Aspect 15, wherein the composite material before crosslinking comprises 50 wt% to 95 wt% of the thermoplastic polymer, 0 wt% to 10 wt%, or 0.25 wt% to 10 wt% of the crosslinking aid, 0 wt% to 5 wt%, or 0.01 wt% to 5 wt% of the curing initiator, 0 wt% to 2 wt%, or 0.0001 wt% to 2 wt% of the additive composition, and 5 wt% to 50 wt% of the ceramic filler composition, based on the total weight of the composite material before crosslinking, and the total is 100 wt%.

[0104] Aspect 17. The cured shaped dielectric component of any one of Aspects 1 to 16, wherein the cured shaped dielectric component has a dielectric constant less than or equal to 6, less than 6, or between 1.1 and 6 measured at 10 GHz.

[0105] Aspect 18. A cured shaped dielectric component according to any one of Aspects 1 to 14, wherein the composite material before crosslinking comprises 10 wt% to 50 wt% of the thermoplastic polymer, 0 wt% to 10 wt%, or 0.25 wt% to 10 wt% of the crosslinking aid, 0 wt% to 5 wt%, or 0.01 wt% to 5 wt% of the curing initiator, 0 wt% to 2 wt%, or 0.0001 wt% to 2 wt% of the additive composition, and 50 wt% to 90 wt% of the ceramic filler composition, based on the total weight of the composite material before crosslinking, and the total is 100 wt%.

[0106] Aspect 19. A cured shaped dielectric component according to Aspect 18, wherein the composite material before crosslinking comprises 10 wt% to 25 wt% of the thermoplastic polymer, 0 wt% to 10 wt%, or 0.25 wt% to 10 wt% of the crosslinking aid, 0 wt% to 5 wt%, or 0.01 wt% to 5 wt% of the curing initiator, 0 wt% to 2 wt%, or 0.0001 wt% to 2 wt% of the additive composition, and 75 wt% to 90 wt% of the ceramic filler composition, based on the total weight of the composite material before crosslinking, and the total is 100 wt%.

[0107] Aspect 20. A cured shaped dielectric component according to any one of Aspects 1 to 19 or 1 to 14 or 16 to 17, wherein the composite material comprises greater than 20 volume %, preferably greater than 40 volume %, of the ceramic filler based on the total volume of the composite material.

[0108] Aspect 21. A cured shaped dielectric component according to any one of Aspects 1 to 20 or 1 to 14 or 18 to 20, wherein the cured shaped dielectric component has a dielectric constant measured at 10 GHz greater than 6, preferably greater than 10, preferably greater than 12.

[0109] Aspect 22. A cured shaped dielectric component according to any one of Aspects 1 to 21, wherein the linear dimension change of the component before curing compared to after curing is less than 2%, preferably less than 1%, in one or two or more linear dimensions.

[0110] Aspect 22a. A cured shaped dielectric component according to any one of aspects 1 to 21, wherein the volumetric size of the component changes by less than 2%, preferably less than 1%, before curing compared to after curing.

[0111] Aspect 23. A cured shaped dielectric component according to any one of Aspects 1 to 22, wherein the component is a dielectric resonator antenna, a dielectric portion of a dielectric resonator antenna, an electromagnetic waveguide, a dielectric electromagnetic lens, a radio frequency component, a microwave component, a millimeter wave component, a terahertz component, or an optical component.

[0112] Aspect 24. A cured shaped dielectric component according to any one of Aspects 1 to 23, wherein the component is a dielectric electromagnetic lens, or a dielectric electromagnetic lens configured to operate at a frequency greater than 5 GHz and less than 300 GHz.

[0113] Aspect 25. A circuit material or circuit substrate comprising the cured shaped dielectric component according to any one of aspects 1 to 24.

[0114] Aspect 26. A method for manufacturing a cured shaped dielectric component according to any one of Aspects 1 to 24, the method comprising: compounding a composite material comprising a thermoplastic polymer having a low processing temperature, an optional crosslinking aid, an optional curing initiator, an optional additive composition, and a ceramic filler composition; melting the compounded composite material to form a melt; shaping the melt to form a shaped article; and exposing the shaped article to radiation to generate sufficient free radicals in the thermoplastic polymer to crosslink at least a portion of the thermoplastic polymer to form the cured shaped dielectric component.

[0115] Aspect 27. The method according to aspect 26, further comprising forming the shaped article on a substrate, masking at least a portion of the shaped article from radiation, and exposing an unmasked portion of the shaped article to radiation to form the cured shaped dielectric component.

[0116] Aspect 28. The method according to aspect 27, wherein shaping comprises molding or forming a layer, preferably molding.

[0117] Articles, compositions and methods may alternatively comprise, consist of, or consist essentially of any suitable material, step or component disclosed herein. Compositions, methods and articles may additionally or alternatively be formulated to be free of or essentially free of any material (or substance), step or component that is not otherwise necessary to achieve the function or purpose of the compositions, methods and articles.

[0118] The term without a clear quantifier modification does not mean a limited number, but means that there is at least one mentioned item. Unless the context clearly indicates otherwise, the term "or" means "and / or". The reference to "one aspect", "another aspect", "some aspects", etc. throughout the specification means that the specific elements (e.g., features, structures, steps or characteristics) described in the embodiment are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the described elements can be combined in any suitable manner in multiple embodiments. As used herein, the terms "first", "second", etc. do not represent any order, amount or importance, but are used to distinguish one element from another element. The term "combination" includes blends, mixtures, alloys, reaction products, etc. In addition, "at least one" or "a combination thereof" is open, and means that the list includes independent individual elements, and a combination of two or more elements in the list, and a combination of at least one element in the list with unnominated similar elements. Unless otherwise defined, the technical terms and scientific terms used herein have the same meaning as the meanings commonly understood by those skilled in the art to which the present disclosure belongs.

[0119] Unless otherwise indicated herein, all test standards are the most current standards in effect as of the filing date of the present application or, if priority is claimed, the filing date of the earliest priority application in which the test standard appears. The endpoints of all ranges involving the same component or property are inclusive, independently combinable, and include all intermediate points and ranges. For example, the range of "up to 25% by weight, or 5% by weight to 20% by weight" includes the endpoints of the range of "5% by weight to 25% by weight" and all intermediate values, such as 10% by weight to 23% by weight, etc.

[0120] Standard nomenclature is used to describe compounds. For example, any position that is not substituted by any specified group is understood to be filled with the bond or hydrogen atom shown in its valence. A dash ("-") that is not between two letters or symbols is used to represent the point of attachment of a substituent. For example, -CHO is connected by the carbon of a carbonyl group. As used herein, the term "(meth)acryloyl" includes both acryloyl and methacryloyl. As used herein, the term "(iso)cyanurate" includes both cyanurate and isocyanurate.

[0121] All cited patents, patent applications, and other references are incorporated herein by reference in their entirety. However, if a term in the present application contradicts or conflicts with a term in the incorporated reference, the term in the present application takes precedence over the conflicting term in the incorporated reference.

[0122] Although specific embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents that are not currently foreseeable or may not currently be foreseeable may occur to the applicant or those skilled in the art. Therefore, the appended claims, as submitted and as may be amended, are intended to cover all such alternatives, modifications, variations, improvements, and substantial equivalents.

Claims

1. A cured shaped dielectric component comprising A cross-linked product of a composite material, the composite material comprising Thermoplastic polymers, Optional crosslinking aids, Optional curing initiator, optional additive composition, and Ceramic filler compositions; wherein the cured shaped dielectric component has a dielectric constant of 1.1 to 20 at 10 GHz, and wherein the cured shaped dielectric component has no melt flow index when tested according to ASTM D1238-20 at 190°C, 2.16 kg, wherein the thermoplastic polymer comprises polyethylene, and The ceramic filler comprises fumed silica, titanium dioxide, or a combination thereof.

2. The cured shaped dielectric component of claim 1, wherein the thermoplastic polymer has a processing temperature of 160°C to 280°C.

3. The cured shaped dielectric component of any one of claims 1 or 2, wherein the thermoplastic polymer has a melting temperature of 90°C to 250°C.

4. The cured shaped dielectric component of any one of claims 1 or 2, wherein the thermoplastic polymer has a melt flow index of less than 5 g / 10 min as measured at 190°C, 2.16 kg according to ASTM D1238-20.

5. The cured shaped dielectric component of any one of claims 1 or 2, wherein the thermoplastic polymer comprises low density polyethylene or linear low density polyethylene.

6. The cured shaped dielectric component of any one of claims 1 or 2, wherein the cross-linked product comprises residues of a cross-linking aid.

7. The cured shaped dielectric component of any one of claims 1 or 2, wherein the cross-linked product does not contain residues of a cross-linking aid; and wherein the thermoplastic polymer comprises a thermoplastic polymer that self-cross-links upon irradiation.

8. The cured shaped dielectric component of any one of claims 1 or 2, wherein the cure initiator is present and has an initiation temperature higher than a processing temperature of the thermoplastic polymer.

9. The cured shaped dielectric component of any one of claims 1 or 2, wherein at least one or more of the cross-linking aid, the cure initiator, or the additive composition is present.

10. The cured shaped dielectric component of any one of claims 1 or 2, wherein the crosslinking aid is present and comprises triallyl cyanurate, triallyl isocyanurate, triallyl phosphate, polybutadiene, zinc diacrylate, zinc dimethacrylate, divinyl benzene, vinyl terminated polyphenylene ether oligomers, m-phenylene bismaleimide, trimethylolpropane trimethacrylate, tetramethylene glycol diacrylate, trifunctional acrylate, dipentaerythritol pentaacrylate, or a combination thereof.

11. The cured shaped dielectric component of any one of claims 1 or 2, wherein the additive composition is present and comprises an antioxidant, a metal deactivator, a processing aid, an adhesion promoter, or a combination thereof.

12. The cured shaped dielectric component of any one of claims 1 or 2, wherein the ceramic filler has a multimodal particle size distribution, wherein a peak of a first mode of the multimodal particle size distribution is at least seven times greater than a peak of a second mode of the multimodal particle size distribution.

13. The cured shaped dielectric component of any one of claims 1 or 2, wherein the composite material comprises prior to crosslinking 10 to 99 wt. % of said thermoplastic polymer, 0 wt % to 10 wt %, or 0.25 wt % to 10 wt % of the crosslinking aid, 0 wt % to 5 wt %, or 0.01 wt % to 5 wt % of the curing initiator, 0 wt % to 2 wt %, or 0.0001 wt % to 2 wt % of the additive composition, and 1 wt % to 90 wt % of the ceramic filler composition, Each is based on the total weight of the composite material before crosslinking, and the total adds up to 100% by weight.

14. The cured shaped dielectric component of claim 13, wherein the composite material prior to crosslinking comprises 50% to 95% by weight of said thermoplastic polymer, 0 wt % to 10 wt %, or 0.25 wt % to 10 wt % of the crosslinking aid, 0 wt % to 5 wt %, or 0.01 wt % to 5 wt % of the curing initiator, 0 wt % to 2 wt %, or 0.001 wt % to 2 wt % of the additive composition, and 5 to 50 wt % of the ceramic filler composition, Each is based on the total weight of the composite material before crosslinking, and the total adds up to 100% by weight.

15. The cured shaped dielectric component of any one of claims 1 or 2, wherein the dielectric constant measured at 10 GHz is from 1.1 to 6.

16. The cured shaped dielectric component of any one of claims 1 or 2, wherein the composite material prior to crosslinking comprises 10 to 50 wt. % of said thermoplastic polymer, 0 wt % to 10 wt %, or 0.25 wt % to 10 wt % of the crosslinking aid, 0 wt % to 5 wt %, or 0.01 wt % to 5 wt % of the curing initiator, 0 wt % to 2 wt %, or 0.001 wt % to 2 wt % of the additive composition, and 50 wt % to 90 wt % of the ceramic filler composition, Each is based on the total weight of the composite material before crosslinking, and the total adds up to 100% by weight.

17. The cured shaped dielectric component of claim 16, wherein the composite material prior to crosslinking comprises 10 to 25 wt. % of said thermoplastic polymer, 0 wt % to 10 wt %, or 0.25 wt % to 10 wt % of the crosslinking aid, 0 wt % to 5 wt %, or 0.01 wt % to 5 wt % of the curing initiator, 0 wt % to 2 wt %, or 0.001 wt % to 2 wt % of the additive composition, and 75 wt % to 90 wt % of the ceramic filler composition, Each is based on the total weight of the composite material before crosslinking, and the total adds up to 100% by weight.

18. The cured shaped dielectric component of any one of claims 1 or 2, wherein the composite material comprises greater than 20 volume percent of the ceramic filler, based on the total volume of the composite material.

19. The cured shaped dielectric component of any one of claims 1 or 2, having a dielectric constant greater than 6 when measured at 10 GHz.

20. The cured shaped dielectric component of any one of claims 1 or 2, wherein the component has a linear dimension that changes by less than 2% in any or all linear dimensions before curing compared to after curing.

21. The cured shaped dielectric component of any one of claims 1 or 2, wherein the component is a dielectric resonator antenna, a dielectric portion of a dielectric resonator antenna, an electromagnetic waveguide, a dielectric electromagnetic lens, a radio frequency component, a microwave component, a millimeter wave component, a terahertz component, or an optical component.

22. The cured shaped dielectric component of any one of claims 1 or 2, wherein the component is a dielectric electromagnetic lens.

23. A circuit material or circuit substrate comprising the cured shaped dielectric component according to any one of claims 1 or 2.

24. A method of making a cured shaped dielectric component according to any one of claims 1 to 22, the method comprising: compounding a composite material comprising the thermoplastic polymer, the optional crosslinking coagent, the optional cure initiator, the optional additive composition, and the ceramic filler composition; melting the compounded composite material to form a melt; shaping the melt to form a shaped article; as well as The shaped article is exposed to radiation to generate sufficient free radicals in the thermoplastic polymer to crosslink at least a portion of the thermoplastic polymer to form the cured shaped dielectric component.

25. The method according to claim 24, further comprising: forming the shaped article on a substrate, shielding at least a portion of the shaped article from radiation, and The unmasked portion of the shaped article is exposed to the radiation to form the cured shaped dielectric component.

26. The method of claim 25, wherein the shaping comprises molding or forming a layer.

Citation Information

Patent Citations

  • Surface treatment agents and polymers comprising substituted phenyl silanes and siloxanes

    US4756971A

  • Thermal conductive composite material and preparation method thereof, and product comprising composite material

    CN109536140A

  • Low loss, composite layer and a composition for forming the same

    CN113840726A

  • Moldable thermosetting composition

    GB2204588A

  • Substrate composition and substrate prepared therefrom

    US20190177527A1